Intraoperative Ocular Decompression Retinopathy During 23 Gauge Transconjunctival Vitrectomy: A Case Report - Agarwal L; Pradhan D; Agrawal N; Joshi I; Kumari A; Kushwaha A (International Medical Case Reports Journal, 2019)
Lalit Agarwal,1 Deepti Pradhan,1 Nisha Agrawal,2 Ichhya Joshi,1 Archana Kumari,1 Anamika Kushwaha1 1Biratnagar Eye Hospital, Biratnagar, Nepal; 2Taparia Eye Care, Biratnagar, NepalCorrespondence: Deepti PradhanBiratnagar Eye Hospital, Rani, Biratnagar, NepalTel +977 9808119112Email deeptiprdhn@gmail.comPurpose: To report an uncommon case of intraoperative ocular decompression retinopathy (ODR).Case report: A 48-year-old man presented with decreased vision and pain in the left eye (LE) for 10 days following trauma with a bamboo stick. He had visual acuity of counting finger close to face in the same eye, along with corneal edema, dilated pupil and posteriorly dislocated lens. Intraocular pressure (IOP) was 42 mm of mercury (Hg). He underwent 23-gauge pars plana vitrectomy with removal of the dislocated lens. Towards the end of otherwise uneventful surgery, blot hemorrhages appeared over the posterior pole and equator. The following day, his vision was counting finger close to face and IOP was 16 mm of Hg. Fundus examination revealed large blotches of hemorrhages at different levels of the retina, later confirmed by optical coherence tomography. Disc hyperfluorescence and blocked fluorescence corresponding to blot hemorrhages were seen on fundus fluorescein angiography. Blood investigations to rule out blood dyscrasias were within normal limits.Conclusion: Ocular decompression retinopathy, though not common, has been reported to occur following various types of surgeries, especially if associated with preoperatively raised IOP. The event can also occur intraoperatively and the preoperative control of IOP is of paramount importance in the prevention of ODR.Keywords: pars plana vitrectomy, intraoperative complication, preoperative raised intraocular pressure, retinal hemorrhages, decompression retinopathy